KEANEKARAGAMAN CENDAWAN RIZOSFER PADA TANAMAN TALAS SATOIMO - Eka Wisdawati; Tutik Kuswinanti; Ade Rosmana; Andi Nasruddin (Agroplantae: Jurnal Ilmiah Terapan Budidaya dan Pengelolaan Tanaman Pertanian dan Perkebunan, 2019)
Rhizosphere is an ideal zone for microorganisms to grow and develop abundantly that influenced by plant roots exudates. Soil microorganisms have a symbiotic mutualism interaction with plants and their interaction influenced the availability of organic soil compound. Therefore, there is a need to investigate and analyze the diversity of fungi at the rhizosphere of economically important food crop like shutterstock taro potato (Satoimo). The study was conducted through several steps as follows: collection of soil samples, dilution of soil samples and isolation of fungi, identification and analyzing of variability of the isolates. The results showed that Satoimo rhizosphere had a diversity index 2.85 which was categorized as a modest index. This result indicated the stability of the fungi community at the Satoimo rhizosphere and its diversity as modest category. The diversity of the microorganisms for each soil sample indicate its organic compounds and as an important factor that determine quality and soil healthy status. Keywords: diversity, rhizosphere, fungi, organic matter